2015
DOI: 10.1038/npp.2015.278
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Oxytocin Affects Amygdala Functional Connectivity after Trauma Script-Driven Imagery in Distressed Recently Trauma-Exposed Individuals

Abstract: Approximately 10% of trauma-exposed individuals go on to develop post-traumatic stress disorder (PTSD). Neural emotion regulation may be etiologically involved in PTSD development. Oxytocin administration early post-trauma may be a promising avenue for PTSD prevention, as intranasal oxytocin has previously been found to affect emotion regulation networks in healthy individuals and psychiatric patients. In a randomized double-blind placebo-controlled between-subjects functional magnetic resonance (fMRI) study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 74 publications
4
41
2
Order By: Relevance
“…Effects of oxytocin in the VMPFC appear to be more indirect than those in the amygdala (Petrovic et al , 2008; Meyer-Lindenberg et al , 2011), consistent with this region’s role in the top-down regulation of amygdala function (Phelps et al , 2004) and its more general role as a hub for integrating affective signals that bear on decision-making (Bechara et al , 1994; Rangel and Hare, 2010; Padoa-Schioppa and Cai, 2011). Consistent with the above, a recent study found that oxytocin administration shortly after experiencing trauma decreased amygdala-VMPFC functional connectivity during trauma related imagery when compared to placebo (Frijling et al , 2015). …”
Section: Introductionsupporting
confidence: 61%
“…Effects of oxytocin in the VMPFC appear to be more indirect than those in the amygdala (Petrovic et al , 2008; Meyer-Lindenberg et al , 2011), consistent with this region’s role in the top-down regulation of amygdala function (Phelps et al , 2004) and its more general role as a hub for integrating affective signals that bear on decision-making (Bechara et al , 1994; Rangel and Hare, 2010; Padoa-Schioppa and Cai, 2011). Consistent with the above, a recent study found that oxytocin administration shortly after experiencing trauma decreased amygdala-VMPFC functional connectivity during trauma related imagery when compared to placebo (Frijling et al , 2015). …”
Section: Introductionsupporting
confidence: 61%
“…However, in our amygdala-centred functional connectivity paradigm (chapter 5; Frijling et al, 2016b), we concluded that the observed effects of oxytocin administration did not fit the salience processing theory, as oxytocin increased amygdala-posterior insula functional connectivity, whereas anterior insula function is generally implicated in salience processing (Menon & Uddin, 2010; Seeley et al, 2007). Of note, we did not investigate whether oxytocin administration affected (anterior) insula functional reactivity, which would have provided important additional information with respect to oxytocin administration effects on salience processing.…”
Section: Discussionmentioning
confidence: 75%
“…With respect to trauma, after the baseline visit of a randomized clinical trial testing the effects of 40 IU of twice-daily OT on the development of symptoms of PTSD among emergency department patients within two weeks of trauma, a single dose of IN OT was shown to increase amygdala reactivity to fearful faces, 119 and, in response to trauma reminders, reduced amygdala-ventromedial PFC connectivity and increased amygdala–insula functional connectivity. 120 This is potentially due to increased salience of fear stimuli during the sensitive post-trauma recovery period. 121,122 However, effects of single versus repeated administration appear to differ, with repeated IN OT administration potentially required to achieve clinically significant effects among high-risk individuals.…”
Section: Treatment Opportunitiesmentioning
confidence: 99%